The Impact of Industrial Era 4.0 and Social Media Marketing on Zakat Payments: A Study of E-Commerce and Online Applications by Zakat Institutions Bogor - Ardyan Renaldy; Moh. Mas'udi (Journal of Islamic Economic and Business Research, 2023)
This study aims to determine the potential of the 4.0 era and the influence of social media marketing activity on online zakat payments through e-commerce and online applications for zakat institutions in terms of the opinions and knowledge of the people of Bogor Regency and City. The data collection technique was done through direct interviews with 35 respondents aged 17-55. The determination of respondents used a purposive sampling technique. This study used a descriptive qualitative method. The primary data was obtained by distributing questionnaires online to respondents, and secondary data was brought based on a literature review. The data analysis was conducted by collecting information from primary and secondary data and then processed to the drawing conclusion. The results of the study show that some people who choose to pay Zakat online have several reasons, such as still wanting to empower the surrounding environment, so to pay Zakat maal, they prefer to pay offline because they can also stay in touch with neighbors and amil zakat. But many of them agree and support the use of social media marketing activity because it is easier and more practical to implement.